Association between second mesiobuccal canal and apical periodontitis in retrospective cone-beam computed tomographic images - ERÇALIK YALÇINKAYA, ŞEBNEM (My University, 2023)
This retrospective cone-beam computed tomography study aimed to investigate the possible associations of apical periodontitis (AP) with missed/unmissed second mesiobuccal (MB2) canals. MB2 canals and AP were investigated in 257 endodontically treated and 673 untreated maxillary molars, and the former were analyzed regarding missed/unmissed MB2 canals. The chi-squared test and odds ratio (OR) were used for statistics. The prevalence of MB2 canals in maxillary first molars was higher than that in second molars (p = 0.001). MB2 canals were 1.751 times more common in males than in females (OR: 1.751; 95% CI: 1.334-2.297), with a significant difference in the 18-39 age groups (p = 0.005). The risk for AP was 5.5 times greater in endodontically treated maxillary molars with missed MB2 canals than in those with unmissed MB2 canals (p = 0.012) (OR: 5.5, 95% CI: 1.549-19.527). The findings of this study reveal that the likelihood of the MB2 canal is higher in the maxillary first molars of young adult males.
Keywords: Tıp; Sağlık Bilimleri; Diş Hekimliği; Medicine; Health Sciences; Dentistry; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; apical periodontitis; cone-beam computed tomography; maxillary molars; second mesiobuccal canal; ENDODONTICALLY TREATED TEETH; MAXILLARY 1ST MOLARS; PERIAPICAL RADIOGRAPHY; ROOT; PREVALENCE; MORPHOLOGY; ACCURACY; LESIONS; CBCT; apical periodontitis; cone-beam computed tomography; maxillary molars; second mesiobuccal canal